Search Deterrence - Armstrong, Mark; Zhou, Jidong (Review of Economic Studies, 2016)
We study sales techniques which discourage consumer search by making it harder or more expensive to return to buy after a search for alternatives. It is unilaterally profitable for a seller to deter search under mild conditions, but sellers can suffer when all do so. When a seller cannot commit to its policy, it exploits the inference that those consumers who try to buy later have no good alternative, and in many cases the outcome is as if the seller must make an exploding offer. Search deterrence results in sub-optimal matching of products to consumers and often raises the price consumers pay.